Kebijakan Luar Negeri Tiongkok dalam Merespon Kebijakan Rebalance Amerika Serikat (AS) di Asia Pasifik tahun 2011 - Hamidah, Irdatul (Global and Policy Journal of International Relations, 2015)
ABSTRACTThis research discusses about the kind and nature of China's foreign policy post US rebalance policy in Asia-Pacific in 2011. The background of this research is the exist of US rebalance policy in Asia Pacific which is considered by China as a US move to stem the power and influence of China in the Asia Pacific region. Those became the main platform issues examined in this study, namely how is the foreign policy of China in responding to US rebalance policy in Asia Pacific. Those problems will be analyzed and explained by using defensive realism theory as a basis of argument. From the theoretical approach that given, it can be deduced that China‘s foreign policy is defensive that is implemented with peripheral diplomacy policy and increase national security and defense through the formulation of defensive strategy.Keywords: Foreign policy, Rebalance, Defensive realism, Peripheral diplomacy, Defense strategyDOI:https://doi.org/10.33005/jgp.v3i02.1938